Instilment of Entrepreneurship Values at Pondok Pesantren Wirausaha Kebon Cinta - Tasiman, Tasiman; Dian Wisika Prajanti, Sucihatiningsih; Pujiati, Amin (Journal of Economic Education, 2021)
esantren (traditional Islamic boarding school) as an educational institution is increasingly facing advanced and more problems must be solved as soon as possible. It needs intensive development to support its growth, nobility, and awakening directly to the community. The purpose of this research is to analyze the process of cultivating entrepreneurial values ​​in Kebon Cinta entrepreneurship pesantren (Pondok Pesantren Kebon Cinta), especially concerning independence and cooperation, and what obstacles are faced in the cultivation process of entrepreneurial values. In this research, the researchers use qualitative research technique because the objects to be studied are values, attitudes, behaviors, and symbols, where the problems tend to be unclear, holistic, complex, dynamic, and full of meaning, so it is impossible for data on the social situation to be analyzed using a quantitative method that uses some instruments such as questionnaires and interviews. Also, researchers analyze social situations in depth. The instilment of entrepreneurial values ​​in the Pondok Pesantren Kebon Cinta is intended to instill a sense of independence and cooperation among santri (students of pesantren) so that they can face the increasingly stringent challenges of the world of work and compete and form partnerships with all levels of society using their communication and adaptability skills they have learned. There are only a few numbers of ustadz (male teachers) and ustadzah (female teachers) who can teach and guide santri in teaching entrepreneurship/skills at the Pondok Pesantren Kebon Cinta. This pesantren is currently trying to find appropriate solutions to the shortage of ustadz/ustadzah who can support the entrepreneurship skills of santri by establishing cooperation from various parties.